(untitled) (Eurasian Journal of Ecology, 2016)
Our study was carried out on the northern macroslope At-Bashy ridge Inner Tien-Shan of Kyrgyzstan. Are described formation leading to the dominance Caraganniks : Caragana jubata and Caragana pleiophylla.